PENGARUH EKUITAS MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP LOYALITAS KONSUMEN SEMEN GRESIK DI KOTA GRESIK - MOCHAMAD NA’IN (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
Good brand equity can be made one of consideration of consumer in purchasing a product. In taking care of its the product Semen Gresik always takes care of and maintains planted brand equity either in its the consumer marrow, so that acceptable Semen Gresik carefully by public. This research aim to know brand equity influence, quality of product, and the price of to consumer loyality Semen Gresik. This research type is associative. this Penelitinan done in town Gresik to cover District Manyar, District Kebomas, and District Gresik. Sample is taken with technique non probability sampling is obtained responder to amount to 100. Data collecting applies questionaire, here in after data with doubled linear regression test.Result of research shows value tcount for brand equity variable ( X1) 3,228, value tcount for variable quality of product ( X2) 2,638, value tcount for price variable ( X3) 3,175, third the number if it is compared to ttabel ( 1,984) hence tcount >ttabel. Based on t test result means there is positive influence of brand equity, quality of product, and the price of to consumer loyality. Test F shows Fcount 17, 897 > Ftabel 2,70 at df=96. Means there is influence in simultan which significant brand equity, quality of product, and the price of to consumer loyality. Based on result of research is expected [by] PT Cement of Indonesia (Persero) Tbk. permanent of maintain product brand equity Semen Gresik through the media, increases quality of product and determine selling price doesn't too height and doesn't boost up price that consumer loyality still awake.